PENGEMBANGAN BAHAN AJAR HAND OUT DENGAN PENDEKATAN KOMUNIKATIF PADA TEKS PROSEDUR SISWA KELAS VII SEKOLAH MENENGAH PERTAMA NEGERI 7 KOTA TANJUNGPINANG - Norahsikin; Isnaini Leo Shanty; Tety Kurmalasari (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2024)
This study aims to describe the development of Hand Out Teaching Materials with a Communicative Approach to the Text Procedure of Class VII Students of Sekolah Menengah Pertama Negeri 7 Tanjungpinang City by conducting validity and practicality tests. This research is a research and development using a 4D model with stages of defining, design, and development. Data collection at Sekolah Menengah Pertama Negeri 7 Tanjungpinang City on a population of 498 students and sampled as much as 10% of each class then obtained a sample of 52 students. The results of the study: 1) produced hand out teaching materials with a communicative approach. 2) Hand out teaching materials with a communicative approach meet very good criteria with the results of material validation by material experts obtained a percentage of 82.5% and the results of teaching material validation by teaching material experts obtained a percentage of 81.5%, so that hand out teaching materials with a communicative approach are feasible to be implemented to students. 3) The practicality of hand-out teaching materials with a communicative approach by students obtained a percentage of 81.8% with very practical criteria